Gulai Kambing Menggunakan Fibercreme Sebagai Pengganti Santan - I Gusti Made Iwan Dusanta Martadjaja (JURNAL GASTRONOMI INDONESIA, 2022)
Coconut milk is one of the ingredients in making lamb curry, however, coconut milk that is cooked for a long time and heated repeatedly can be a source of bad fat and contains high cholesterol so that people with certain diseases such as acid reflux disease or GERD, high blood pressure, diabetes, and coconut milk allergy cannot consume coconut milk. Therefore, in this study coconut milk is replaced with FiberCreme. Replacement of coconut milk using FiberCreme when viewed from its superiority is considered effective to prevent or reduce the risk of an increase in cholesterol and bad fats in the blood. This study aims to determine the quality of lamb curry cooked with FiberCreme in terms of taste, aroma, texture, and color. This research was assessed by distributing questionnaires to 25 panelists. All assessments given by the panelists will be calculated using the Likert scale method. Based on the final results of the organoleptic test, lamb curry products using FiberCreme have good quality as seen from the average interpretation of 79.5%, which is seen from the assessment of taste, aroma, texture, and color.